The Relations of Internal and External Factors with Women Farmers’ Participation in Rice Farming Activities - Pratiwi, Dita; Yusalina, Yusalina; Baga, Lukman Mohammad (Universitas Sebelas Maret, 2021)
The participation of women in the agricultural sector has increased in the last two years, attributed to the population growth and household economy. Therefore, this research examined the internal and external factors to the women farmers’ participation. This research was conducted in Situ Gede Village, West Bogor Sub-district, Bogor City and involved women farmer group consisting of 36 members. The primary data were gathered by interviewing respondents using a questionnaire, while the secondary data were obtained from literature review and various related institutional sources. The data were examined using the Pearson’s Product-Moment Correlation analysis to investigate the relations between the internal and external factors to women farmers’ participation. The results of this study have revealed the internal factors related to women farmers’ participation, such as age, farm experience and decision making. Meanwhile, the external factor related to the participation of women farmers is the access to counseling, meaning that some of these aspects need to receive the government’s attention, especially in terms of access to education related to the counseling method, time and substance of counseling.